(untitled)
We will present two new results for the ’’Dirichlet eta’’ function \(S(s) =_n≥ 1(-1)^n n^s \) which would lead us to announce a new conjecture equivalent to that of the Rieman Hypothesis. , number=1, journal=Journal of Informatics and Mathematical Sciences, year=2024, month=Dec., pages=47–56